THE EFFECT OF EXCHANGE RATE ON NON PERFORMING FINANCING IN SHARIA BANK IN INDONESIA - Lilis Renfiana (Al Birru: Jurnal Keuangan dan Perbankan Syariah, 2022)
ABSTRACT Non-performing financing is one of the bank's performance functions, because: a high NPF (Non Performing Financing) ratio is an indicator of failure bank in managing a business. This study aims to analyze and test how much influence Exchang Rate has on NPF (Non-Performing Financing) in Islamic Commercial Banks in Indonesia Indonesia. This research uses quantitative research. Population in This research is the annual financial report data of Islamic Banks in Indonesia registered with Bank Indonesia (BI) obtained from publication data from each each Sharia Commercial Bank website in 2015-2020. Research sample determined with use method purposive sampling and in earn as many as 14 samples. The analytical technique used in this research is descriptive statistical analysis, classical assumption test (normality test, multicollinearity test, test heteroscedasticity, test autocorrelation), and analysis regression linear multiple with IBM program help SPSS Statistics 25. Results study this state that Inflation is not take effect Significant to NPF. Keywords: Non-Performing Financing, Exchange Rate, Sharia Commercial Banks